Efektivitas Unit Clarifier, Filtrasi, Desifeksi dan Reservoir di Instalasi Pengolahan Air ( IPA ) 2 Krian - Nu'aimah, Zena; Novirina Hendrasarie (Jurnal Serambi Engineering, 2025)
The Water Treatment Plant (WTP) 2 Krian plays a vital role in ensuring the quality of drinking water that meets health standards. This study aims to evaluate the effectiveness of the clarifier, filtration, disinfection and reservoir units in reducing raw water turbidity. A quantitative method was employed through direct field measurements using a turbidity meter, focusing on turbidity removal percentages (% removal) over the period of May 22–28, 2025. The results showed that the clarifier unit consistently achieved high turbidity removal efficiency, ranging from 97.72% to 98.72%. The filtration unit also demonstrated stable performance, with turbidity removal percentages between 59.65% and 72.41%. The final turbidity values were below 3 NTU, in complied with Indonesian Ministry of Health Regulation No. 2 of 2023. Collectively, the four units functioned effectively to support safe and potable water treatment. This evaluation serves as a critical basis for maintaining and improving the performance of the WTP to ensure sustainable clean water supply.